INTERNET JOURNALISM: OPPORTUNITIES AND CHALLENGES (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article analyzes the development of internet journalism, its role in modern society, opportunities, and emerging challenges. Internet journalism has accelerated the dissemination of information, enabled access to a global audience, and strengthened direct interaction with readers through interactivity. However, it also faces significant challenges, including fake news, information security, and ethical issues. The article examines both positive and negative aspects of internet journalism, its prospects, and the difficulties it currently encounters.